2009
DOI: 10.1007/s12603-009-0209-4
|View full text |Cite
|
Sign up to set email alerts
|

Validated treatments and therapeutics prospectives regarding pharmacological products for sarcopenia

Abstract: Loss of physical function in older adults may be, at least in part, explained by sarcopenia, a phenomenon characterized by a reduction in number and size of muscle fibres and by increase in interstitial fat and connective tissue. Lifestyle intervention (i.e. physical activity and nutrition) have shown to impact on sarcopenia. However, several drugs were suggested, with various levels of scientific evidence, to have an impact on muscle outcomes. In this study we reviewed the effect of six classes of drugs on sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 154 publications
(134 reference statements)
1
17
0
1
Order By: Relevance
“…Many studies have shown that ACEIs have favorable effect on physical function. The mechanisms for effects of ACEIs on skeletal muscle may be concluded as muscle fiber type effect which determines a shift of the myosin-heavy chains of leg skeletal muscle from type II toward type I, Anti-inflammatory effect, nutritional effect, effects on angiogenesis and metabolic effect [54]. Our result showed that ACEIs could not improve gait speed and grip strength significantly, indicating that ACEIs could not improve physical function in elderly, which was inconsistent with the results from animal experiments [55][56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that ACEIs have favorable effect on physical function. The mechanisms for effects of ACEIs on skeletal muscle may be concluded as muscle fiber type effect which determines a shift of the myosin-heavy chains of leg skeletal muscle from type II toward type I, Anti-inflammatory effect, nutritional effect, effects on angiogenesis and metabolic effect [54]. Our result showed that ACEIs could not improve gait speed and grip strength significantly, indicating that ACEIs could not improve physical function in elderly, which was inconsistent with the results from animal experiments [55][56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…86 Examples are angiotensin-converting enzyme (ACE) inhibitors, statins, testosterone, growth hormones and oestrogen. 115,116 Despite some early promising results, however, it is currently difficult to recommend these pharmacological agents as part of a routine clinical treatment. Studies to date have not only been small in size, but have at times provided conflicting results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…116 Some authors have shown that growth hormone and testosterone are able to increase muscle mass and in some cases strength in older persons [117][118][119][120][121][122] but clinicians should be cautious with such treatments because of the adverse effects and because the benefit tends to disappear when these agents are withhold.…”
Section: Proteinmentioning
confidence: 99%